Study on the Capital of Domestic Health Funds in an Environment of Interest Rates Close to Zero - Tóth, Balázs; Csiki, Máté; Kiss, Gábor Dávid (Public Finance Quarterly, 2019)
Along with demographic, social and technological changes, the burden on the public health care system will grow with the increase in public health expenditure from the central budget; meanwhile, private expenditures continue to snatch a larger piece. The system of health funds is of paramount importance for health care financing and long-term financial planning. However, in 2010, the reserves behind the membership and increasing contributions and thus the accumulated capital were exhausted. In our study, we will examine the factors influencing the capital reserves of health insurance funds with the help of a vector autoregression (VAR) model, focusing on three specifications: the internal processes, the capital market and the health care system. The sample covers the period between 1998 and 2018, with annual data related to all health funds. According to specific models, used memberships, bond markets’ yields, and life-span expectancy have a positive impact on the accumulation of funds by health insurance funds; nevertheless, the information available on the Internet may depreciate enthusiasm towards investment.